Penerapan Regresi Data Panel pada Permasalahan Tingkat Pengangguran Terbuka Di Jawa Barat - Siti Fatonah; Fenny Fitriani; Artanti Indrasetianingsih (Mathematics Department, Faculty of Mathematics and Sciences Unisda Lamongan, 2023)
The indicator used to measure unemployment is the Open Unemployment Rate (TPT). West Java Province is a high-ranking TPT contributor province and during 2018-2021 is always in the top three compared to other provinces in Indonesia. West Java has a different unemployment rate every year and between districts / cities. Panel data regression is a regression technique that combines time series data and corss section. In estimating panel data regression models, there are three approaches, namely the Commond Effect Model (CEM), Fixed Effect Model (CEM) and Random Effect Model (REM). To choose the best model, it uses three tests, namely the Chow test, the Hausman test and the Lagrange Multiplier test. In this study, regression analysis of panel data was carried out to determine the factors that influence the open unemployment rate in West Java province. The results of the analysis obtained the best model of FEM between individuals and time with an R2 value of 0.9410 or 94.10%. Factors that have a significant effect on the open unemployment rate are the district/city minimum wage, education index and percentage of poor people